Integrating Multiple Perspectives Into an Impact Mitigation Program for Sustainable Whale and Dolphin Tourism Management - Ferdin, Arockia E. J.; Jhong, Yan-Cheng; Lee, Chun-Hung (Frontiers in Conservation Science, 2022)
Balancing the sustainable practices of whale watching and cetacean species conservation is an enormous challenge for the countries that rely on whale watching tourism industry. In this study, we employ the Choice experiment method to estimate the tourists’ heterogeneity preferences (THP) on different attributes to establish an impact mitigation program in Taiwan. We found that the scenario of integrated cetacean conservation and sustainable whale-dolphin watching has the highest welfare effects among all the proposed scenarios. Features that affect the differentiation of THP are: 1) tourists' awareness, and conservation attitudes, 2) nationality and 3) monthly income. The findings from this research could assist the government and tour operators to tailor their policy and management strategy that respond to the present issues by focusing on time schedule management, vessel slowdown distance, set up maximum boat numbers, build-up operational guidance, and by establishing a conservation fund.